1996
DOI: 10.1177/027507409602600406
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Enterprise Activities as Revenue Generators: A Different View

Abstract: Enterprise funds provide one means by which cities provide municipal goods and services to their residents while generating revenues to augment cities' other revenue-generating activities or substitute for other forms of revenue. Because municipal enterprises are accounted for in separate proprietary funds, determining the extent to which the revenues they generate are actually usable by non-enterprise functions is somewhat more difficult than we have generally presumed. I use data from a recent national surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…behalf of each type. In terms of privatization decisions and possible deregulation effects, it means that cities with electric power enterprises should be extremely cautious about making any decision that might reduce the exceptional revenue-generating effects of these enterprises (Stumm, 1996;Stumm & Khan, 1996). In summary, Florida's electric power enterprises are not adopting TQM as extensively as might be expected in view of the initial success experienced by Florida Power and Light.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…behalf of each type. In terms of privatization decisions and possible deregulation effects, it means that cities with electric power enterprises should be extremely cautious about making any decision that might reduce the exceptional revenue-generating effects of these enterprises (Stumm, 1996;Stumm & Khan, 1996). In summary, Florida's electric power enterprises are not adopting TQM as extensively as might be expected in view of the initial success experienced by Florida Power and Light.…”
Section: Resultsmentioning
confidence: 99%
“…The major benefit, however, is the amount of revenue that these enterprises provide cities in an era of fiscal strain. Stumm (1996) found that this revenue averaged over $3 million, or about $77 per resident.…”
Section: Introductionmentioning
confidence: 99%
“…These incentives often include tax increment financing and abatements, freeports or enterprise zones. Some government enterprises require subsidization, but a majority generate annual surpluses which help to defray local tax burdens and provide services in-kind (Stumm 1996). Many public corporations of this type are targets of privatization by special interests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are largely self-supporting, may provide capital for their infrastructure and growth needs through revenue bonds rather than municipal general obligation bonds, and they generate significant amounts of revenue (Gitajn 1984;Pierce and Rust 1991). Although this revenue must be transferred to other municipal funds prior to use for non-enterprise activities, it nonetheless constitutes a significant portion of municipal revenues for cities that employ such enterprises (Stumm 1996). As community development agencies, municipal enterprises have proven successful in a wide variety of circumstances, and can function well in inter-local settings.…”
Section: Privatization Versus Public Enterprisementioning
confidence: 99%
“…Local public enterprise has a long and noteworthy history in the United States. Governments have traditionally owned and operated utility enterprises in areas such as electricity, water, sewer, and solid waste collection, as well as nonutility enterprises, such as airports and seaports, civic centers, public parking facilities, recreational facilities, public transportation systems, hospitals, and emergency services (Stumm, 1996). Such traditional forms of public ownership play an important role in stabilizing the economies of communities, in generating securely rooted jobs, and especially, in providing local governments with a substantial source of revenues.…”
Section: Six Modelsmentioning
confidence: 99%